2023
DOI: 10.1002/acp.4148
|View full text |Cite
|
Sign up to set email alerts
|

Functions of episodic future thinking: A validation and comparative study across individuals with normal versus pathological worry

Mehdi Akbari,
Shiva Jamshidi,
Mohammad Seydavi
et al.

Abstract: Future thinking is the ability to mentally simulate future scenarios, events, or circumstances that one might be personally involved in. The present study sought to evaluate the Persian version of the Functions of Future Thinking Scale (FoFTS) in a large sample of the Iranian general population and to compare individuals with normal versus pathological worry. The Persian FoFTS had an acceptable 10‐factor structure and the reliability index of all factors was within an acceptable range. The validity was explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
0
0
Order By: Relevance
“…Du, Hallford, and Busby Grant's (2022) review indicated that most studies had been conducted in community samples, and few involved samples selected on the basis of clinically elevated levels of anxiety. Within these clinical samples characterized by elevated anxiety, compared to non-anxious samples, differences in future thinking have been observed, for example, more overgeneral future thinking in posttraumatic stress disorder (Brown et al 2013;Kleim et al 2014;Verfaellie et al 2024), and more negatively biased and less vivid future thinking in Generalized Anxiety Disorder (GAD) (Wu et al 2015; also, please see Akbari et al 2023). Although few studies exist that have examined the effects of induced state anxiety, the evidence in community samples indicates that state anxiety may not affect the ability to generate specific future events, but it may affect the detailed elaboration of these future events (Hallford et al 2019;Zhou, Li, and Hu 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Du, Hallford, and Busby Grant's (2022) review indicated that most studies had been conducted in community samples, and few involved samples selected on the basis of clinically elevated levels of anxiety. Within these clinical samples characterized by elevated anxiety, compared to non-anxious samples, differences in future thinking have been observed, for example, more overgeneral future thinking in posttraumatic stress disorder (Brown et al 2013;Kleim et al 2014;Verfaellie et al 2024), and more negatively biased and less vivid future thinking in Generalized Anxiety Disorder (GAD) (Wu et al 2015; also, please see Akbari et al 2023). Although few studies exist that have examined the effects of induced state anxiety, the evidence in community samples indicates that state anxiety may not affect the ability to generate specific future events, but it may affect the detailed elaboration of these future events (Hallford et al 2019;Zhou, Li, and Hu 2024).…”
Section: Introductionmentioning
confidence: 99%